The Protective Activity of Penehyclidine Hydrochloride against Renal Ischemia/Reperfusion-Mediated NLRP3 Inflammasome Activation is Induced by SIRT1. Issue 5 (4th May 2022) - Liu, Zhaohui; Meng, Yanli; Wei, Qianjie; Miao, Yu; Yu, Lili; Li, Yuqing; Zhang, Bing
Abstract: Background: The activation of alveolar macrophages (AMs) modulated via leucine-rich repeat (NLR) pyrin domain containing 3 (NLRP3) inflammasome activation is key to the progression of renal ischemia/reperfusion (rI/R)-mediated acute lung injury (ALI). Sirtuin-1 (SIRT1) can attenuate NLRP3 inflammasome activation during I/R stress and may be an important mechanism underlying ALI pathogenesis. Penehyclidine hydrochloride (PHC), an anticholinergic drug, exerts protective effects against rI/R-mediated ALI. This study aimed to decipher the effects of PHC on SIRT1 activation and the underlying mechanism of the protective activity of PHC against rI/R-mediated ALI.Materials and methods: We used an ALI rat model and the rat AMs cell line NR8383 to assess the degree of lung injury in vivo and in vitro .Results: The results show that PHC attenuates rI/R-mediated lung injury indices, myeloperoxidase, and apoptosis in vivo . It decreases the rI/R-mediated release of prostaglandin E2 and nitric oxide, mitochondrial reactive oxygen species production, and the activity of NADPH oxidase-4 in vitro . PHC ameliorates the rI/R-induced activation of the thioredoxin-interacting protein, caspase 1 (P10 unit), and NLRP3 inflammasome, along with reduced activation of interleukin-1β and interleukin-18 in vitro . We show that PHC alleviates the rI/R-induced reduction of SIRT1 and the depletion of SIRT1 eliminates the ameliorating activity of PHC on the NLRP3 inflammasome activation in vitro . Conclusions: In summary, the findings suggest that PHC ameliorates the rI/R-mediated ALI through the SIRT1-mediated NLRP3 inflammasome activation.